Analisis Kebutuhan Modul Ajar Berbasis Realistic Mathematics Education untuk Meningkatkan Kemampuan Representasi Matematis Peserta Didik - Aflah, Tania; Maimunah, Maimunah; Hutapea, Nahor Murani (Media Pendidikan Matematika, 2026)
Mathematical representation skills are one of the key competencies that students need to possess in mathematics learning. However, various studies indicate that students’ mathematical representation skills remain relatively low, particularly in translating contextual problems into visual, symbolic, or verbal forms. This study aims to analyze the need for the development of teaching modules based on Realistic Mathematics Education (RME) to support students’ mathematical representation skills in the subject matter of linear equations and inequalities with one variable. This study employs a qualitative descriptive approach. The research subjects consist of two mathematics teachers and 32 eighth-grade students at MTs Negeri 1 Bengkalis. Data collection techniques included interviews and tests of mathematical representation skills. Data analysis was conducted through curriculum analysis, content analysis, and analysis of student characteristics. The research findings indicate that teachers have not yet developed teaching modules independently and still rely on learning materials obtained from the internet or colleagues. Additionally, students’ mathematical representation skills remain relatively low, with 31% demonstrating visual skills, 22% symbolic skills, and 47% verbal skills. The research findings indicate that there is a need to develop RME-based teaching modules that align with students’ characteristics, learning materials, and the requirements of the Merdeka Curriculum.